Pengaruh Kampanye Public Relations #BeautyDiQuity terhadap Brand Awereness Luxcrime - Mutiara Fathiyah Subagyo; Siska Yuningsih (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2024)
The #BeautyDiQuity campaign is a campaign created by a local makeup and skincare brand with the aim of empowering women to feel beautiful and charming, regardless of any conditions, by featuring models with disabilities as Luxcrime ambassadors. In addition to collaborating with models with disabilities, Luxcrime also sells bundled product packages at a special price, with ten percent of the sales from these packages being donated to the disabled community in Yogyakarta. The purpose of this research is to measure the public relations campaign #BeautyDiQuity, assess Luxcrime's brand awareness, and evaluate the extent of the impact of the public relations campaign on Luxcrime's brand awareness. The study utilizes public relations campaign theory (awareness, attitude and opinion, and behavior) and brand awareness theory (unaware of brand, brand recognition, brand recall, top of mind). The research method employed is quantitative with a survey research approach. Data collection involves administering questionnaires to 66 respondents. The results of the study indicate a moderate influence of the #BeautyDiQuity campaign on Luxcrime's brand awareness, with a value of 0.522 or 52.2%. This suggests that 52.2% of Brand Awareness is influenced by the Public Relations campaign, while the remainder is influenced by other factors.